Legal Implications in Flood Management in Thailand - Phornsuphanwong, Chakrawan (Law for Development Graduate Journal, 2024)
This independent research aimed to study legal measures in water management during floods in Thailand, which correlated with structural problems deriving from law ambiguity and misalignment with disaster management principles, including before, during, and after flooding. Respectively, ambiguity in the roles of local administration for flood management as well as in work delegation of disaster management has been significant. The study also evaluated legal measures in flood management in foreign countries, namely Japan and French Republic, for comparison analysis and recommendations towards appropriate legal measures in Thailand. The study implied that legal measures in flood management in Thailand have caused structural issues from overlapping roles of government entities that are misaligned with general principles in disaster management, as well as issues within local administration in disaster management that is inconsistent with the principles of decentralization or self-governance in local level. In addition, there has proven to be low involvement from citizens and private sector in disaster management, which is not parallel with community-based disaster management principle. Such circumstance has thoroughly rooted from the structure of Thailand public administration. From the study and evaluation of legal measures in foreign countries, results have shown that Japan has established disaster-management laws as General Law, has systematic disaster-management structures, and has clear allocation of accountabilities between public and private sectors. On the other hand, French Republic has enabled legal measures in disaster forecast, warning system, rescue system, and recovery and mitigation. All measures are aimed to prioritize risk reduction and damage prevention, consistent with global disaster-management principles, by allocating responsibilities to local administration in preventing and managing disaster. With aforementioned factors, author recommends to incorporate more provisions in accountability of government entities as the authority of Disaster Prevention and Mitigation, authorize Disaster Prevention and Mitigation Act 2007 as General Law pertaining common disaster management, and elevate the roles of local administration in disaster management before, during, and after the disasters. Roles of private sector and citizens in disaster management should also increase. Community-wise, local citizens should be educated with disaster management principles to strengthen the knowledge, awareness, and sense of responsibility towards community and environment, which would contribute to cost reduction from government entities in disaster management and would possibly reduce damage in lives and properties respectively.